Hiperrealitas Makna Kesenangan dalam Iklan Bertema Gaya Hidup di Media Sosial - Anastasia Yuni Widyaningrum; Yuli Nugraheni (Jurnal Kawistara, 2021)
This study aims to reveal the meaning in the language used in pleasure-filled advertisements which are related to lifestyle. The concept of pleasure refers to hedonism which means prioritizing happiness and avoiding sadness or suffering. Ads about body care, travel and shopping are used as the subject of study. Using the analytical method of semiotic sign map of Charles Sanders Peirce, which consist of icons-indexes and symbols, this study analyzes the advertisements on Facebook and Istagram offering lifestyle from September through December 2020. Analysis is based on Baudrillard’s hyperreality and consumerism combined with the study of leisure time, hedonism and lifestyle. As the result, this research has identified terms used in verbal language of the advertisements i.e ‘lawan tanda penuaan’, ‘menyamarkan’, ‘mencerahkan’, ‘serasa’, ‘book now fly later’, ‘gajian’, ‘saatnya belanja’. Meanwhile, non-verbal signs consist of travel accommodation, lodging, blue sky, plants and temples in Bali. The analysis found that the advertising language leads to forgetting or getting away from real conditions and does not offer happiness itself. Pleasure capitalism is the heart of the advertisements offer. The conclusion of the research has shown that Semiotic sign system in the advertisements has became to maximize hyperreality.